22 Design and Implementation of A Nutrition Clinical Pathway for Patients with Fractured Neck of Femur. (6th February 2020) - Kingdon, J; Aadan, H; Husain, S; Atkinson, C; Thomson, C; Braude, P
Abstract: Background: Patients with a fractured neck of femur (FNOF) are commonly malnourished pre-admission, have reduced oral intake in hospital and a hypermetabolic state up to three months postoperatively (E Paillaud 2000). Malnutrition is associated with functional deterioration, higher morbidity and mortality. Evidence suggests nutritional supplementation post-surgery can reduce postoperative complications. As a result, nutritional assessment is included in the National Hip Fracture Database best practice tariff (Avenell, Cochrane Database of Systematic Reviews 2016). Introduction: Our aim was to design and implement a clinical pathway for patients with FNOF to identify malnutrition and provide appropriate nutritional support. Intervention: A retrospective audit of 25 patients was completed to understand baseline rates of assessment, prescription of supplements and referral to dietetics. Using these data meetings were arranged to develop a clinical pathway. Key stakeholders included dietetics, orthopaedic surgeons, geriatricians, physiotherapists and nurses. The pathway was evaluated and optimised with two Plan-Do-Study-Act (PDSA) cycles looking at 25 patients each time. Results: Baseline: 79% received a nutritional assessment, 32% had nutritional supplements prescribed and 36% (n=9) met criteria for referral to a dietician, of which 55%were referred. However, an additional 5 referrals were made to dietetics for patients who did not meet criteria, a 50% inappropriate referral rate. PDSA cycle 1: increased nutritional assessment (85%), increased nutritional supplements prescribed (92%), decreased inappropriate referrals to dietetics (43%). PDSA cycle 2: increased nutritional assessment & nutritional supplements prescribed (100%), increased inappropriate referrals to dietetics (80%). Conclusions: The implementation of a nutrition pathway has led to increased identification and treatment of malnutrition, which has in addition improved accrual of the best practice tariff. However, greater number of inappropriate referrals have been made to dietetics. This is partly attributed to difficulty weighing patients on admission, and where no weight is inputted on the Malnutrition Universal Screening Tool a "High Risk" score is generated triggering a referral. We are now looking at alternative methods to obtaining a weight such a mid-upper arm circumference.